Daisaikoto for Menstrual Pain: A Lesson from a Case with Menstrual Pain Successfully Treated with Daisaikoto - Yuko Horiba; Tetsuhiro Yoshino; Kenji Watanabe (Case Reports in Medicine)
Menstrual pain is one of the common symptoms among women. It is estimated that 5–14% of women are sometimes absent from school or work because of pain. Usually gynecologists prescribe analgesics and/or low-dose oral contraceptives. However, such treatment is not always effective and sometimes causes an adverse effect, such as stomach pain or low body temperature. Kampo medicine is one of the choices for the menstrual pain in Japan. Tokishakuyakusan, kamishoyosan, or keishibukuryogan is commonly used for the treatment of menstrual pain. Here we report a case of menstrual pain successfully treated with daisaikoto which is not commonly used for such a case. Twenty-five-year-old woman suffered from severe menstrual pain and stress at company. She also had constipation and abdominal distension. We prescribed daisaikoto extract 7.5 g per day. Not only menstrual pain but also constipation and abdominal distension improved within 6 months. Here we propose that daisaikoto is one of the choices for the treatment of menstrual pain with mental stress.